Transversal Lightlike Submersions - Cumali Yıldırım; Esra Karataş (Journal of Advanced Research in Natural and Applied Sciences)
In this paper, we introduce the concept of transversal lightlike submersions from semi-Riemannian manifolds onto semi-Riemannian manifolds. Specifically, we present the concepts of transversal r-lightlike and isotropic transversal lightlike submersions and examine the geometry of foliations formed by these submersions through various examples. In this way, we demonstrate certain points where transversal r-lightlike submersions differ from semi-Riemannian submersions. Furthermore, we investigate O’Neill’s tensors for transversal r-lightlike submersions and examine the integrability of certain distributions by employing these tensor fields. Thus, valuable information regarding such submersions’ geometric structures and properties can be provided, paving the way for new research avenues. We finally discuss the need for further research.